Putting the t in tools: a roadmap for implementation of new global and regional transgender guidance. (17th July 2016) - Wolf, R Cameron; Adams, Darrin; Dayton, Robyn; Verster, Annette; Wong, Joe; Romero, Marcela; Mazin, Rafael; Settle, Edmund; Sladden, Tim; Keatley, JoAnne
Abstract : Transgender (trans) activists and global health partners have collaborated to develop new tools and guidance for assessing and addressing HIV and other health needs within trans populations. Trans women experience a heavy burden of HIV and other sexually transmitted infections (STIs), high incidence of violence and difficulties accessing gender‐affirming services. At the same time, little has been published on trans men's health, HIV issues, needs and experiences. Young trans people are especially marginalized and vulnerable, with few programmes and services specifically tailored to their needs. Trans‐specific data and guidance are needed to adapt the global response to HIV to meet the needs of the trans population. While the needs of this group have only recently received attention, global, regional and other technical guidance documents are being developed to address these gaps. Regional blueprints for comprehensive care for trans people in Latin America, the Caribbean, and Asia and the Pacific are now available. These tools – supported by the Pan American Health Organization, World Health Organization, US President's Emergency Plan for AIDS Relief and the United Nations Development Programme, in collaboration with regional trans groups – provide a contextual map, indicating opportunities for interventions in health, HIV, violence, stigma and discrimination, social protection and human rights. Global guidance includes the World Health Organization's Policy Brief: Transgender People and HIV, and the interagency publication, Implementing Comprehensive HIV and STI Programmes with Transgender People . Community empowerment and capacity building are the focus of the new tools for global and regional transgender guidance. The goal is to strengthen and ensure community‐led responses to the HIV challenge in trans populations. This article describes the new tools and guidance and considers the steps needed to use them to appropriately support and engage transgender populations within national AIDS, STI, and sexual and reproductive health responses and programmes. The time to use these tools and guidance for advocacy, strategic planning, capacity building, programme design and training is now.